Low‐cost recycling production of pectinase to increase the yield and quality of Muzao jujube juice by Aspergillus niger. (20th November 2019) - Yang, Chun; Wang, Jiahong; Chio, Chonlong; Chen, Xuantong; Zhang, Ling; Zhang, Jiangning; Feng, Zhihong; Han, Jiming; Ding, Weiying; Qin, Wensheng
Abstract: A low‐cost recycling system for the production of pectinase was built to improve the yield and quality of Muzao date juice and to reduce production costs. An Aspergillus niger strain, Gyx086, was selected from 20 A. niger strains on potato agar plates containing Muzao date residues, and the strain was used to produce an enzyme cocktail with high pectinase activity using Muzao date residues as the medium. The high pectinase activity level was therefore used in the production of Muzao date juice. Under optimized enzymatic hydrolysis conditions, a date juice yield of 92.88% was obtained, which was 11% higher than the control, and was not significantly different from a commercial preparation. Further storage trials indicated that the clarity, viscosity, storage stability, and soluble solid content could also be greatly improved by enzymatic treatment. These results suggested that the cheap experimental preparation could effectively replace the commercial preparation used for the production of date juice. This is the first systematic report detailing the production of Muzao date juice using a cheap and effective pectinase cocktail, which could promote the development of the date juice industry. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd